Handbook on contemporary issues in health, crime, and punishment - Link, Nathan W.; Novisky, Meghan A.; Fahmy, Chantal (The ASC Division on Corrections & Sentencing handbook series, 2025)
"topics on the numerous ways in which mental and physical health and criminal justice system contact influence one another and are intricately intertwined. These often mutually reinforcing dynamics affect a range of health and justice outcomes at individual, familial, group, community, and national levels. Contributions detail this topic from a wide range of disciplinary, theoretical, and international perspectives and rely on various analytical lenses, including quantitative, qualitative, policy-analytic, theoretical/conceptual, and lived experiences. The chapters summarize what is known in each topical area, but as important, they identify emerging theoretical, empirical, and policy directions. In this way, the book is grounded in the current knowledge about the specific topic, but also provides new, synthesizing material that reflects the knowledge of the leading minds in the field. Conceptually divided into eleven sections, a number of contributions describe the unique experiences of women, people of color, juveniles, older populations, immigrants, LGBTQ+ individuals, and other sub-populations (i.e., people convicted of drug or sex offenses). Where appropriate, the authors provide both big picture and pragmatic policy directions aimed at reducing system contact, health challenges, and inhumane practices. Given its breadth and depth, the Handbook will appeal broadly to academics, practitioners, policymakers, advocates, and students seeking to understand the many ways in which health and justice system dynamics overlap"--